Genetic diversity analysis of wild tea plant resources in Chongzuo based on phenotypic traits and SSR molecular markers - Zongyou Wei; Feifei Wu; Hongyu Feng; Ziping Li; Qinhao Jian; Yunxiong Zhao; Baogui Liu; Jinting Li (PLoS ONE, 2025)
To explore the genetic diversity of wild tea plants, the methods of the phenotypic traits and SSR molecular marker analysis were adopted to analyze the 40 samples of 7 wild tea populations in Chongzuo, Guangxi. The results showed that the coefficient of variation of 18 descriptive phenotypic traits ranged from 15.76% to 50.64%, and the diversity index ranged from 0.38 to 1.04. The coefficient of variation of the four numerical phenotypic traits ranged from 31.91% to 56.86%. The diversity index ranged from 1.70 to 1.93. Based on phenotypic trait clustering, the 40 tea plant samples were divided into three distinct groups. A total of 117 alleles (Na) were detected by 14 pairs of SSR primers. The polymorphism information content (PIC) of primers ranged from 0.25 to 0.87. The study showed that the optimal K value for population number, based on genetics, was 2. Meanwhile, the genetic distance among populations ranged from 0.24–0.74, the percentage of variation among populations was 20.46%. The genetic distance between the 40 tea plant resources ranged from 0.20–0.95, and the percentage of variation between individuals was 74.22%. When the individual genetic distance was 0.33, the 40 tea plant resources were divided into three groups. This study elucidates the genetic diversity of 40 wild tea plant accessions from seven populations in Chongzuo, Guangxi, which can provide a theoretical basis for breeding superior tea cultivars and conserving tea plant resources.